Digital Learning Readiness of Pre-Service Elementary Teachers in Myanmar: Perceptions of Learning Management Systems and Human Resource Management Implications - Thet, Min Min; Rahadi, Dedi Rianto (Indonesian Journal of Teaching and Teacher Education, 2025)
The integration of Learning Management Systems (LMS) has become increasingly significant in higher education, particularly in contexts where access to face-to-face learning is disrupted. This qualitative phenomenological study investigates pre-service elementary teachers’ perceptions of Learning Management System use in Myanmar, focusing on their experiences at a University of Teaching. Data were collected through semi-structured interviews and a focus group discussion involving twelve pre-service elementary teachers who had prior experience using Moodle during their coursework. The findings indicate that participants generally perceived LMS as a useful and flexible tool that supported access to learning materials, facilitated revision through recorded lectures, promoted autonomous learning, and reduced costs related to transportation and physical resources. However, participants also reported significant challenges, including unstable internet connectivity, technical system limitations, restricted access to downloadable materials, and insufficient system notifications. In addition to technical barriers, psychological challenges such as boredom, loneliness, reduced motivation, and lack of social interaction were identified. These findings suggest that while LMS plays an essential role in sustaining teacher education in Myanmar, particularly under unstable conditions, its effectiveness is constrained by infrastructural and emotional factors. The study highlights the need for improved technological infrastructure, enhanced system design, and supportive pedagogical strategies to strengthen LMS implementation in pre-service elementary teacher education.